The ABCs of reading an ECG - Shalihin, Mohd Shaiful Ehsan (Malaysian Medical Gazette, 2015)
Reading ECG is important not only for emergency medicine, but also for any medical personnel. Having systematic approach, but easy to be followed is definitely helpful, not only for detecting common problems, but also not to miss any gross findings. Here is one of the approaches, by looking each component according to sequences. Starting with counting the heart rate & determine the rhythm, followed by cardiac axis and ventricular hypertrophy, then intervals and looking at each P wave, QRS complex, ST segment and T waves.